Content of Copper, Iron, Iodine, Rubidium, Strontium and Zinc in Thyroid Malignant Nodules and Thyroid Tissue adjacent to Nodules - Vladimir Zaichick (Journal of Clinical and Diagnostic Pathology, 2022)
Thyroid malignant nodules (TMNs) are the most common endocrine cancer. The etiology and pathogenesis of TMNs must be considered as multifactorial. Diagnostic evaluation of TMNs represents a challenge, since there are numerous benign and malignant thyroid disorders that need to be exactly attributed. The present study was performed to clarify the possible role of some trace elements (TEs) as cancer biomarker. For this aim thyroid tissue levels of copper (Cu), iron (Fe), iodine (I), rubidium (Rb), strontium (Sr), and zinc (Zn) were prospectively evaluated in malignant tumor and thyroid tissue adjacent to tumor of 41 patients with TMNs. Measurements were performed using energy-dispersive X-ray fluorescent analysis. Results of the study were additionally compared with previously obtained data for the same TEs in “normal” thyroid tissue. From results obtained, it was possible to conclude that the common characteristics of TMNs in comparison with “normal” thyroid and visually “intact” thyroid tissue adjacent to tumor were drastically reduced level of I. It was supposed that the drastically reduced level of I content in cancerous tissue could possibly be explored for differential diagnosis of benign and malignant thyroid nodules.
Keywords: Thyroid